2016
DOI: 10.1002/cmdc.201600387
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, and Evaluation of Dasatinib–Amino Acid and Dasatinib–Fatty Acid Conjugates as Protein Tyrosine Kinase Inhibitors

Abstract: Derivatives of dasatinib were synthesized via esterification with 25 carboxylic acids including amino acids and fatty acids by extending the inhibitor to interact with more diverse sites and to improve specificity. Dasatinib-L-arginine derivative (Das-R, 7) was the most potent of the inhibitors tested with IC50 values of 4.4 nM, <0.25 nM, and <0.45 nM against Csk, Src, and Abl kinases, respectively. The highest selectivity ratio obtained in our study, 91.4 Csk/Src belonged to compound 18 (Das-C10) with an IC50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 53 publications
(104 reference statements)
1
14
0
Order By: Relevance
“…(3) Dasatinib completely blocked Src phosphorylation on Y527 by another PTK, Csk [39], and significantly inhibited Src autophosphorylation on Y416. This is consistent with earlier reports that both Src and Csk are sensitive to dasatinib [40]. Dasatinib also appeared to partially inhibit Mek and Erk activation, suggestive of crosstalk between Src and the MAP kinase pathway.…”
Section: Src Ir/igf-1r/akt Signaling and The Map Kinase Pathway Are supporting
confidence: 92%
“…(3) Dasatinib completely blocked Src phosphorylation on Y527 by another PTK, Csk [39], and significantly inhibited Src autophosphorylation on Y416. This is consistent with earlier reports that both Src and Csk are sensitive to dasatinib [40]. Dasatinib also appeared to partially inhibit Mek and Erk activation, suggestive of crosstalk between Src and the MAP kinase pathway.…”
Section: Src Ir/igf-1r/akt Signaling and The Map Kinase Pathway Are supporting
confidence: 92%
“…Dasatinib is a multitargeted inhibitor. Previous studies demonstrated that dasatinib exhibited strong inhibition of ABL and BCR/ABL tyrosine kinases and broad activity against Src-family tyrosine kinases (2224). Dasatinib is a second-generation tyrosine kinase inhibitor.…”
Section: Discussionmentioning
confidence: 99%
“…Wild‐type human Abl catalytic domain, full‐length Csk, FGFR1 catalytic domain, and full‐length Lck were cloned into pGEX‐4 T‐1 plasmid using BamHI and EcoRI restriction sites as described previously and expressed in E. coli DH5α. All constructs were verified by sequence analysis.…”
Section: Methodsmentioning
confidence: 99%